Incarceration as violence: inflicting pain in Portuguese prisons - Frois, C.; Bento, A. (Revista Crítica de Ciências Sociais, 2019)
This article sets the groundwork for understanding prison violence as a broad and interrelated phenomenon which is bound by shifting notions of legitimacy. We argue that the concept of violence can help understand how the “pains of imprisonment” are inflicted and punishment is produced in different prison settings. Drawing upon fieldwork carried out in several Portuguese prisons, we describe how unequal sets of circumstances are imposed on groups of inmates, who become differently exposed to the deprivations of confinement. Our argument is that the various types of prison violence should be understood against this backdrop, as well as relationship to the diverse circumstances in which they are produced and the subjectivities of the individuals involved.